Leber's Hereditary Optic Neuropathy is Associated with Compound Primary Mutations of Mitochondrial ND1 m.3635G > A and ND6 m.14502 T > C. (9th December 2015) - Jin, Xin; Wang, Lifeng; Gong, Yan; Chen, Bing; Wang, Yanhua; Chen, Tingjun; Wei, Shihui
Abstract: Purpose : To describe the clinical and molecular characteristics of a Chinese Leber hereditary optic neuropathy (LHON) pedigree with compound mitochondrial DNA (mtDNA) mutations of m.3635G > A and m.14502T > C. Methods : A total of 22 individuals (2 affected, 20 unaffected) from a five-generation Chinese family with LHON underwent comprehensive ophthalmic examination, including visual acuity, slit lamp examination, fundoscopy, visual field examination and visual evoked potentials (VEP). The complete mtDNA genome of the two patients were amplified by polymerase chain reaction, sequenced using a Bigdye terminator v3.1 cycle sequencing kit and analyzed on an ABI 3700XL Genetic Analyzer. Results : Two LHON patients in the family presented typical features of LHON: painless and progressive deterioration of bilateral vision, bilateral optic atrophy, centrocecal scotomata in both eyes and significant prolonged P100 latency and low amplitude potential in VEP. Compound primary mtDNA mutations of m.3635G > A and m.14502T > C were identified in these two patients and another 12 living matrilineal members of the pedigree. Haplogroup analysis showed the patients in this LHON family belonged to the N9b1 haplogroup. Modeled mutant structure showed the mutations altered the molecular local space conformation on the surface of ND1 and ND6. Conclusions : Compound mtDNA mutations of m.3635G > A and m.14502T > C presented with low penetration, and the patients with these compound mutations exhibited mild visual impairment. The biological information analysis suggested that m.14502T > C might play a protective role in LHON associated with m.3635G > A. The haplogroup analysis indicated that the mtDNA haplogroup might be an important factor affecting the expression of LHON associated with m.3635G > A and/or m.14502T > C.